Competence communication discipline and work environment on employee performance - Ade Suryanto; Istiatin Istiatin; Sudarwati Sudarwati (Institute of Computer Science (IOCS), 2023)
This study aims to determine the effect of competence, communication, discipline and work environment variables on the performance of employees at Sangkrah Health Center, Pasar Kliwon District, Surakarta City. This research method uses a quantitative research design. The sample in the study was 37 employees at the Sangkrah Health Center, Pasar Kliwon District, Surakarta City. The sampling technique used in this research is the Census technique. Data collection using a questionnaire. The data analysis technique used statistical analysis, namely multiple linear regression test, F test, t-test, and coefficient of determination. The results showed that competence, communication, discipline and work environment had a significant effect on the performance of employees at the Sangkrah Health Center, Pasar Kliwon District.